Studi Efektivitas Ruang Henti Khusus (RHK) Sepeda Motor Pada Simpang Bersinyal - Nainggolan, Jesicha; Purba, Aleksander; Sulistyorini, Rahayu (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2018)
The increasing number of motorcycle vehicles, causing traffic congestion at the signal intersection in Bandar Lampung City. As an effort in reducing congestion, the government of Bandar Lampung city made Special Stopping Space (RHK) for motorcycles. The RHK is a space dedicated to arrange motorcycle queue place when stop at the signalized intersection during traffic light period. This study aims to examine the effectiveness of RHK at the signalized intersection, and it’s impact on saturation current increase and approach capacity compared to approach without RHK. The effectiveness and impact of RHK, was conducted by surveying traffic flow in the morning during peak hours using camera video in each selected approaches. The survey data obtained were analyzed using MKJI and compared with previous research. RHK increases saturation flow 7,3% - 17,5% and approach capacity 37,67% - 52,09%. In conclusion RHK is effective to be provided in signal intersection. Value of RHK filling level at Jl. P. Diponegoro - Jl. P. Diponegoro and Jl. Jend. Sudirman - Jl. Gajah Mada - Jl. Jend. Sudirman is less than 50% that indicates bad while at Jl. Jend. Sudirman - Jl. Jend. Sudirman and Jl. Dr. Susilo - Jl. P. Diponegoro is 50% - 80% that indicates moderate.  Keyword : RHK (SSSM : Special Stopping Space for Motorcycle), signal intersection, effectiveness of RHK, saturation current, capacity of the approach